PENGARUH PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN MENGGUNAKAN METODE SOSIODRAMA UNTUK MENANAMKAN KEPEDULIAN SOSIAL SISWA KELAS IV SD SWASTA SEBERANG JAYA TAHUN PELAJARAN 2017/2018 - Abdulah Abdulah (Jurnal Tunas Pendidikan, 2019)
This research is motivated by the lack of student's social attitude. This study aims to determine the effect of learning Civics using sociodrama method to instill social awareness of fourth graders Elementary School Swasta Seberang Jaya. This research is a quasi experimental research with Noquivalent Control Group Design research design.Subjects in this study are the students of class IV consisting of two classes. Class IVB as experiment group, and class IVA as control group. Data collection techniques used in research in the form of scale, interview, observation, and documentation. Test requirements data analysis using the test of normality and homogeneity. Hypothesis testing using t-test with 5% significance level.The results of this study indicate that the learning of Civics using sosiodrama method gives a significant positive impact to instill social awareness of fourth grade students of swasta Elementary School Seberang Jaya 2017/2018. This was demonstrated by a t-test in the experimental-control group post-test, which showed significant differences between experimental-control group post-tests after treatment (treatment).